Anti-inflammatory and anti-insulin resistance activities of aqueous extract from Anoectochilus burmannicus - Phatcharaporn Budluang (2018)
© 2016 The Authors. Food Science & Nutrition published by Wiley Periodicals, Inc. This study investigated biological activities including antioxidative stress, anti-inflammation, and anti-insulin resistance of Anoectochilus burmannicus aqueous extract (ABE). The results showed abilities of ABE to scavenging DPPH and ABTS free radicals in a dose-dependent manner. Besides, ABE significantly reduced nitric oxide (NO) production in the lipopolysaccharide (LPS)-treated RAW 264.7 via inhibition of mRNA and protein expressions of nitric oxide synthase (iNOS). The LPS-induced mRNA expressions of cyclooxygenase-2 (COX-2) and interleukin 1β (IL-1β) were suppressed by ABE. Moreover, ABE exerted anti-insulin resistance activity as it significantly improved the glucose uptake in tumor necrosis factor (TNF)-α treated 3T3-L1 adipocytes. In addition, ABE at the concentration of up to 200 μg/mL was not toxic to human peripheral blood mononuclear cells (PBMCs) and did not induce mutations. Finally, the results of our study suggest the potential use of A. burmannicus as anti-inflammatory, anti-insulin resistance agents, or food supplement for prevention of chronic diseases.